Progression patterns and therapeutic sequencing following immune checkpoint inhibition for hepatocellular carcinoma: An international observational study. (13th January 2023) - Talbot, Thomas; D'Alessio, Antonio; Pinter, Matthias; Balcar, Lorenz; Scheiner, Bernhard; Marron, Thomas U.; Jun, Tomi; Dharmapuri, Sirish; Ang, Celina; Saeed, Anwaar; Hildebrand, Hannah; Muzaffar, Mahvish; et al.
Abstract: Background and Aims: Different approaches are available after the progression of disease (PD) to immune checkpoint inhibitors (ICIs) for hepatocellular carcinoma (HCC), including the continuation of ICI, treatment switching to tyrosine kinase inhibitors (TKIs) and cessation of anticancer therapy. We sought to characterise the relationship between radiological patterns of progression and survival post‐ICI, also appraising treatment strategies. Methods: We screened 604 HCC patients treated with ICIs, including only those who experienced PD by data cut‐off. We evaluated post‐progression survival (PPS) according to the treatment strategy at PD and verified its relationship with radiological patterns of progression: intrahepatic growth (IHG), new intrahepatic lesion (NIH), extrahepatic growth (EHG), new extrahepatic lesion (NEH) and new vascular invasion (nVI). Results: Of 604 patients, 364 (60.3%) experienced PD during observation. Median PPS was 5.3 months (95% CI: 4.4–6.9; 271 events). At the data cut‐off, 165 patients (45%) received no post‐progression anticancer therapy; 64 patients (17.6%) continued ICI beyond PD. IHG (HR 1.64 [95% CI: 1.21–2.22]; p  = .0013) and nVI (HR 2.15 [95% CI: 1.38–3.35]; p  = .0007) were associated with shorter PPS. Multivariate models adjusted for progression patterns, treatment line and albumin‐bilirubin grade and Eastern Cooperative Oncology Group performance status at PD confirmed receipt of ICI beyond PD with (HR 0.17, 95% CI: 0.09–0.32; p  < .0001) or without subsequent TKI (HR 0.39, 95% CI: 0.26–0.58; p  < .0001) as predictors of prolonged PPS versus no anticancer therapy. Conclusions: ICI‐TKI sequencing is a consolidated option in advanced HCC. nVI and IHG predict a poorer prognosis. Despite lack of recommendation, the continuation of ICI beyond progression in HCC is adopted clinically: future efforts should appraise which patients benefit from this approach.